Uji Kompetensi Berbasis Penilaian Diri pada Mata Kuliah Rangkaian Elektronika - Islami, Anggun Variasi (Lembaga Yasin AlSys, 2022)
This study aims to see the activeness, initial competence, material readiness and final competence of students during online lectures. The assessment carried out is a self-assessment or self-assessment. The research method used is descriptive qualitative research with research subjects majoring in Informatics Engineering 2nd semester who take the Electronic Circuit course. The results of this study indicate that the activeness of students in self-assessment is very high. However, learning readiness is still low at only 21%. Likewise with the initial competence where students still answer questions randomly so that there are still many misconceptions. Meanwhile, after the lectures were carried out and students filled out the form again, there was a significant improvement both in terms of students preparing for lectures and also in terms of final competence. The biggest difficulty of self-assessment for remote competency testing is that students can open Google to see answers to questions both during pre-test and post-test. Keywords: self-assessment, competency test